PENGARUH SELF-EFFICACY, BIMBINGAN KARIER, DAN KETERAMPILAN KOMUNIKASI TERHADAP KESIAPAN KERJA SISWA PROGRAM AKUNTANSI DAN KEUANGAN LEMBAGA - Azrokun Nahar; Jarot tri Bowo Santoso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocational High School (SMK) students' work readiness remains a significant concern due to the high rate of salary reductions and the increasingly competitive demands of the industrial world. This study focused on analyzing the influence of self-efficacy, career guidance, and communication skills on students' job readiness in the Accounting and Financial Institutions expertise program. The approach used in this study was a quantitative approach with a survey method involving 108 grade XII students at SMK Negeri 2 Semarang. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that the three variables had a positive and significant effect on students' job readiness. Self-efficacy had the most dominant influence, followed by career guidance and communication skills. Simultaneously, the three variables were able to explain 54.1% of the variation in students' job readiness. These findings confirm that job readiness is not only determined by technical aspects, but is also influenced by psychological factors and non-technical skills. Therefore, efforts are needed to increase self-confidence, optimize career guidance services, and strengthen communication skills to improve the job readiness of vocational high school students.